A Design Methodology for Fit‐for‐Purpose Human Views. Issue 6 (5th December 2016) - Handley, Holly A. H.
ABSTRACT: The Human Views were developed to collect and categorize human‐focused information to ensure that the human component is considered in system architecture development. While the Human Views are not an integrated viewpoint with the Department of Defense Architecture Framework (DoDAF), they can be implemented as a set of Fit‐for‐Purpose views. Fit‐for‐Purpose views are custom views created to address specific stakeholder questions and to display custom sets of data. However, very little guidance exists for the creation of Fit‐for‐Purpose views or their use in architecture analysis. To help address this, a six‐step methodology was developed to design Fit‐for‐Purpose Human Views for the DoDAF. The methodology is illustrated using a mobile communication system; the resulting Human Views can be used to evaluate the impact of assigning different types of personnel to complete mission tasks using the system. By including custom data in the output products, such as simulation outcomes, the Fit‐for‐Purpose views support resolution of specific stakeholder concerns. The six‐step design methodology is domain agnostic and may be generalizable to the design of Fit‐for‐Purpose views for other areas of concern.